Size matters: Associations between the androgen receptor CAG repeat length and the intrafollicular hormone milieu - Borgbo, T; Macek, Milan; Chrudimská, Jana; Jeppesen, J V; Hansen, L L; Andersen, C Yding (Molecular and cellular endocrinology, 2016)
Granulosa cell (GC) expressed androgen receptors (AR) and intrafollicular androgens are central to fertility. The transactivating domain of the AR contains a polymorphic CAG repeat sequence, which is linked to the transcriptional activity of AR and may influence the GC function. This study aims to evaluate the effects of the AR CAG repeat length on the intrafollicular hormone profiles, and the gene expression profiles of GC from human small antral follicles. In total, 190 small antral follicles (3-11 mm in diameter) were collected from 58 women undergoing ovarian cryopreservation for fertility preservation. The biallelic mean of the CAG repeat lengths were calculated for each woman, and grouped in three groups: Long CAG repeats (23-26 mean CAG); medium CAG repeats (20.5-22.5 mean CAG) and short CAG repeats (17.5-20.0 mean CAG). The following parameters were measured: follicle diameter, intrafollicular levels of Anti-Müllerian Hormone (AMH), progesterone, oestradiol, testosterone and androstenedione, and GC gene expression levels of FSHR, LHR, AR, CYP19A1, and AMH. The long CAG repeat lengths were associated with significantly decreased testosterone levels, as compared to medium CAG repeats (P = 0.05) and short CAG repeats (P = 0.003). Furthermore, in follicles 3-6 mm in diameter, the long CAG repeats were associated with significantly increased LHR and CYP19A1 gene expression levels compared to short CAG repeat lengths (P = 0.004 and P = 0.04 respectively), and significantly increased LHR expression compared to medium CAG repeat lengths (P = 0.03). In conclusion, long CAG repeat lengths in the AR were associated to significant attenuated levels of androgens and an increased conversion of testosterone into oestradiol, in human small antral follicles.
Keywords: androgenní receptory; Young Adult; Trinucleotide Repeat Expansion; mladý dospělý; Adolescent; Aromatase; folikulární tekutina; Adult; dospělí; stanovení celkové genové exprese; expanze trinukleotidových repetic; mladiství; Gene Expression Profiling; pohlavní hormony; Gonadal Hormones; receptory LH; lidé; ženské pohlaví; aromatasa; Humans; Receptors, LH; testosteron; Follicular Fluid; Female; Testosterone; Receptors, Androgen